Effectiveness of dual sequential wavelength laser in the treatment of portwine stains - A retrospective study - Mohan Kumar Periyasamy; C Shanmuga Sekar; Reena Rai (Wolters Kluwer Medknow Publications, 2019)
Background: Port Wine Stain (PWS) is only partially and superficially treated with the Pulsed dye laser (PDL) because of its limited depth of penetration. The 1064-nm long pulsed Nd:YAG laser has greater depth of penetration and is used to treat deeper vessels. The dual sequential wavelength laser (DSWL) which combines PDL/Nd:YAG (595/1064 nm) can be more effective for the treatment of deeper, nodular portwine stains due to its synergistic effect. The purpose of this study is to evaluate the efficacy and safety of DSWL in the treatment of portwine stains after five treatment sessions. Materials and Methods: A total of 11 patients with PWS lesions on the head and neck, who were treated with DSWL for at least five sittings at monthly interval were included in this study. The assessment of the therapeutic response and grading of improvement was done with a scale of 0 to 4 by comparing the photographs taken before treatment and after 5 sittings of laser treatment. Results: Out of the 11 patients, 5 patients (45.45%) had more than 70% improvement. Six out of eleven patients (54.54%) had 40 to 70% improvement at the end of five sittings with no adverse effects including purpura. Conclusion: Dual Sequential Wavelength Laser is a good modality of treatment for portwine stains. It has enhanced penetration and effective clearance of thicker, nodular, recalcitrant lesions of PWS. DSWL is safe and efficacious and it can be recommended as a therapeutic modality for portwine stains.